Analisis Kepuasan Pelanggan terhadap Kualitas Pelayanan dengan Metode Servqual, Customer Satisfaction Index dan Importance Performance Analysis pada Yasse Barbershop - Muhammad Nu’man Fathoni; Mohammad Jufriyanto (Jurnal Serambi Engineering, 2022)
Yasse Barbershop is a haircut service business for children to adults. At the beginning of 2019, there were business developments at Yasse, including providing hair facial services, hair massage, relaxation, hair dye services and selling various kinds of hair care products. The innovation was carried out because the owner wanted to improve the completeness of services, satisfy customers and be superior to competitors. The completeness of services at Yasse Barbershop is an attraction for customers. In order to create customer satisfaction so as to create customer loyalty, the quality of service must be proportional to the completeness of the service. This study aims to identify the level of customer satisfaction with the services provided at Yasse barbershop. The Servqual, Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods are the three methods used. Service quality gap analysis results show that all service quality data has a negative gap value. The results of the analysis with CSI showed a customer satisfaction index of 74%. These two things mean that Yasse barbershop customers are not satisfied with the services provided, and service improvement actions are needed